Audio and Computer Cognitive Behavioral Therapy for Depressive Symptoms in Older Adults: A Pilot Randomized Controlled Trial. Issue 6 (November 2018) - Shah, Avani; Morthland, Martin; Scogin, Forrest; Presnell, Andrew; DiNapoli, Elizabeth A.; DeCoster, Jamie; Yang, Xin
Abstract: The purpose of this study was to develop and explore the feasibility of audio-based (ACBT) and computer-based (CCBT) cognitive behavioral therapies for older adults with depressive symptoms. The audio program consisted of 8 compact discs and a workbook while the computer program consisted of 11 modules of similar duration provided on a tablet PC. Both interventions consisted of the following topics: identifying and changing unhelpful thoughts, addressing feelings, relaxation, engaging in pleasant events, assertiveness, and problem-solving. Fifty-one older adults were recruited from medical settings and rural communities. Participants were randomly assigned to immediate treatment (ACBT or CCBT) or delayed treatment control condition. Analyses were conducted to examine change on interviewer-based and self-reported depression. A significant interaction effect between time and condition was found on the interviewer-based depression scale. This suggests that both types of treatments decreased depressive symptoms over time when compared to a delayed treatment control. Computer-based and audio-based cognitive behavioral treatments may be valuable low-cost modalities to deliver psychotherapy to older adults with depressive symptoms. Highlights: Two low cost technological interventions for depression in older adults were developed. Audio and computer cognitive behavioral therapies improved mood compared to a control over time. Older adults reported satisfaction with both types of technology treatments. Over a third of the treatment groups experienced clinically significant improvements.